Effect of multiscale reinforcement by fiber surface treatment with polyvinyl alcohol/graphene oxide/oxidized carbon nanotubes on the mechanical properties of reinforced hybrid fiber composites. (1st March 2021) - He, Yuxin; Chen, Qiuyu; Wu, Dongyang; Zhou, Mengyang; Wang, Tengfei; Lu, Chang; Zhang, Li; Liu, Hu; Liu, Chuntai
Abstract: Polyvinyl alcohol-graphene oxide-oxidized carbon nanotube (PVA-GO-OCNT) hybrid coatings were adopted to modify glass fibers (GFs) and carbon fibers (CFs), and modified GF/CF-reinforced polyurethane hybrid composites (PVA-GO-OCNTs-HFs/PUs) with different concentric hybrid structures were prepared. The synergistic effect of the hybrid structure and surface modification of hybrid fibers (HFs) on the mechanical properties of hybrid composites was investigated systematically. The results show that the hybrid structure can optimize the comprehensive mechanical properties of HF-reinforced composites (HFRCs) by combining the performance advantages of the two types of fiber reinforcement, and the strength of the interface between HFs and polyurethane (PU) plays a crucial role in whether the advantages of the hybrid structure can be fully achieved. In addition, the mechanical properties of the composite were significantly enhanced, and the structural advantages of the hybrid structure were further improved after HFs were modified by PVA-GO-OCNT hybrid coating. The hybrid effect on the tensile strength of HFRCs with CF as the core and GF as the shell changes from a negative hybrid effect (−5.4%) before modification to a positive hybrid effect (4.3%). The hybrid effect in tensile failure strain of HFRCs with GF as the core and CF as the shell changes from a negative hybrid effect (−2.1%) before modification to a positive hybrid effect (2.1%). Moreover, the interlaminar shear strength of HFRCs modified by PVA-GO-OCNT hybrid coating is significantly higher than that of unmodified HFRCs. Graphical abstract: Image 1 Highlights: The surface of hybrid fiber was modified by PVA/GO/OCNTs. Multi-scale structure and chemical activity contribute a lot in composite adhesion. A comparison of hybrid effect before and after interfacial modification is performed. The collaborative reinforcement of the hybrid interface modification and hybrid structure were analyzed.